2019
DOI: 10.9734/ajee/2019/v9i130086
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Odoba Forest Reserve to Livelihoods of the Rural People in Ogbadibo Local Government Area, Benue State, Nigeria

Abstract: The study was conducted to assess the contribution of Odoba forest reserve to rural livelihoods of the communities in Ogbadibo Local Government Area of Benue State, Nigeria. Pre-tested semi-structured questionnaires were administered to three hundred and seventy-six respondents in 188 households in four communities. Data collected were analyzed using descriptive and inferential statistics. Fifteen different wood and non-wood products were collected by the respondents from the forest reserve with fuel wood prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The study found age having significant positive influence on utilization of forest resources from Odoba forest reserve. The mean age of the people was 42 years [22]. This finding agrees with [18] [18] and [28] also confirms this finding.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The study found age having significant positive influence on utilization of forest resources from Odoba forest reserve. The mean age of the people was 42 years [22]. This finding agrees with [18] [18] and [28] also confirms this finding.…”
Section: Discussionsupporting
confidence: 91%
“…Descriptive statistics was used to analyze the socio-economic characteristics of the people as reported in [22]. Probit regression model as used by [18] was as adopted to determine the socioeconomic factors that influenced utilization of forest resources from Odoba forest reserve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations